Bianchi Type 〖VI〗_0 One Dimensional Cosmic String for Bulk Viscous Fluid in f(R,T)Theory of Gravity (International Journal of Scientific Research in Science and Technology, 2025)
In the framework of f(R,T) gravity proposed by Harko et al. spatially homogeneous and anisotropic Bianchi type -〖VI〗_0 cosmological model is considered when the source for energy momentum tensor is a bulk viscous fluid containing one dimensional cosmic string. To solve the field equations completely, we have considered three different cases: (i) the expansion scalar of the space-time is proportional to the shear scalar given by Collins which gives a relationship between metric potentials (ii) the law of variation of Hubble’s parameter proposed by Berman which yields the constant deceleration parameter. (iii) A barotropic equation of state is assumed to get a determinate solution of the field equations. Also, the bulk viscous pressure is assumed to be proportional to the energy density. The physical behaviour of the investigated model is discussed and also the graphical behaviour of some parameters is discussed.